"Either You Do It or You're Going to the Box": Coerced Labor in Contemporary America. (September 2019) - Hatton, Erin
In recent years the problem of precarity has become the primary focus of both popular and academic accounts of work. Yet precarity is not the only troublesome feature of the contemporary economy. In this article I show that coercion—rather than precarity—is central to an array of work relations in the US, including prison labor, workfare, foreign guestwork, undocumented labor, and more. Through ground-level case studies of prison labor and workfare, I examine workers' experience of labor coercion. I then build out from this empirical analysis to theorize the structure of coercive labor regimes and their relationship to precarity. Coercive labor regimes, I argue, are those in which employers have state-sanctioned power over workers' well-being, families, and futures—a power that I call "social coercion." This analysis thus identifies a new arena in which the "ambidextrous" neoliberal state operates in America today.